System of centromeric, episomal, and integrative vectors based on drug resistance markers for Saccharomyces cerevisiae. (January 2006) - Taxis, Christof; Knop, Michael
Integrative, centromeric, and episomal plasmids are essential for easy, fast, and reliable genetic manipulation of yeast. We constructed a system of shuttle vectors based on the widely used plasmids of the pRS series. We used genes conferring resistance to Geneticin® (kanMX4), nourseothricin (natNT2), and hygromycin B (hphNT1) as markers. The centromeric and episomal plasmids that we constructed can be used the same way as the traditional auxotrophic marker-based shuttle vectors (pRS41x andpRS42x series). Additionally, we created a set of nine yeast integrative vectors with the three dominant markers. These plasmids allow for direct integration in the LEU2, URA3, and HIS3 locus of any yeast strain and the concomitant partial deletion of the gene. This prevents multiple integrations and allows for the rapid identification of correct integrants. The set of new vectors considerably enhances the flexibility of genetic manipulations and gene expression in yeast. Most notably, the new vectors allow one to work with natural yeast isolates, which do not contain auxotrophic markers.